The Journal of Molecular Modeling: Impact, expectations and experience - Clark, Timothy; Roth, Henryette (Chimia, 1998)
Experience shows that electronic journals are accepted as long as the quality of the published material is up to the standards of printed journals. Therefore, the aim of an electronic journal is primarily to be a serious scientific publication, and only secondarily an electronic publication. The Journal of Molecular Modeling, published for the first time in 1995, is the first fully electronic journal in chemistry. The aim of the journal is to provide high-quality science and take advantage of the electronic format. From the beginning, the journal was designed as trilogy of on-line, CD-ROM, and printed versions, which guarantees longevity of the published research data, allows access to articles and supplementary material without depending on the Internet, and allows the reader to leaf through the journal in the classical fashion. However, this does not mean that the Journal of Molecular Modeling will always be published in a conservative 'book-like' format. The goal is to find the electronic format that most appeals to readers without sacrificing the scientific quality of the journal. Scientific journals are steadily developing towards active and interactive publications.